The Syndicate Pattern Of The Human Trafficking From The Criminological Perspective In Indonesia - Putri Anissa Salsabilah; Isma Nurillah; Desia Rakhma Banjarani (Universitas Sriwijaya, 2023)
The crime of human trafficking is a transnational crime and become a global concern for countries in all around the world. Indonesia has Law No. 21 Of 2007 concerning Detention of Persons Trafficking Offenders. The purpose of this researchis to find out criminological point of view of human trafficking. The research uses normative methods with doctrine and statutory approaches. The results of the research show that the problem of human trafficking does not only affect one institution, but must involve all community actors, namely. state agencies, non-governmental organizations, municipal organizations joining the state-enhanced partnership, decrees and ministerial decrees together to solve human trafficking problems.